Language And Gender In Teen Short-Stories - Dwi Indarti (Wanastra: Jurnal Bahasa dan Sastra, 2018)
This study aims to investigate the differences of language use between two short-stories published in two teen magazines which represent gender. According to the content, context, and segment readers, HAI magazine is considered as teen male magazine while KAWANKU is considered as teen female magazine. The results of this study confirm the theory of gender in writing production proposed by Coates (1993) who stated that men tend to use a report style aiming to communicate factual information, whereas women more often use a rapport style which is more concerned with building and maintaining relationships.  The two short-stories in HAI and Kawanku reflect the issue of gender construction in society through written discourse. Gendered language that occurs in the literary works such as short-story declare that the differences between male and female way of speak can be found in written texts.